Mountains and Volcanoes - Tylor, Barbara; Nang Chan Yeema (New York. USA Kingfisher Books, 1992)
Examines, in text adn labeeled diagrams adn illustrations, how different types of mountains were formed, the composition of various kinds of rock, volcanic mountains, and the process of erosion. Includes instructions for projects.
Keywords: Juvenile Nonfiction